Studi Empiris Risiko Operasional Sistem Manajemen K3 terhadap Tindakan Tidak Aman (Unsafe Action) pada Industri Maritim - Amanda Br. Harahap, Faiza Dia (PT. Alahyan Publisher Sukabumi, 2024)
The majority of activities in the Multi Terminal Sub-Holding area, which has quite a large work space, involve heavy equipment which can be dangerous. In recent years, there has been a growth in ship operational activities including loading and unloading which has raised various concerns. In the field, there are still many dangers caused by the widespread loading and unloading operations of containers to other modes of transportation, transit of containers to and from holding points or warehouses, as well as ship operations such as berthing and ship docking. In addition, workers' ignorance of safety regulations and procedures, such as the use of personal protective equipment when working, increases the possibility of work accidents. Workers' ignorance of unsafe work positions (unsafe action). This research aims to reveal the K3 management system variables that influence unsafe activities in the Indonesian maritime industry, as well as the elements that influence operational risks, dangerous risks, and control strategies to reduce risks. A unified design with mixed methods was the research approach used. Purposive and snowball triangulation were used to collect qualitative data, while random sampling was used to collect numerical data. Review of empirical evidence regarding factors that influence operational risks that arise when SMK3 is implemented in the maritime industry. These factors include basic causal factors, indirect causal factors due to work and personal factors, as well as direct factors causing work accidents due to unsafe activities and unsafe conditions. carries a significant danger of ineffective and inefficient loading and unloading performance. There is a negative influence between SMK3 on unsafe actions in the maritime industry.